Can Gamification Stimulate Customers to Repurchase in the E-Marketplace? The Mediation Effect of Customer Experience and Engagement - Sarah Alia Djohan; Dennis Handhana; Vicenza Bianca Castafiore; Evelyn Hendriana (Budapest International Research and Critics University, 2022)
Intense competition among e-marketplaces drives companies to find creative ways to attract and keep customers. One of the approaches is by increasing customer engagement in the online community. Customer engagement to the e-marketplace can be enhanced by attaching gamification to the applications to create excitement and a fun experience for the customers when using the application. Despite its potential benefits, there are limited studies of the effect of gamification on repurchase intention. Furthermore, studies that look at the mediating effect of customer experience and engagement are relatively absent. This study examines the influence of gamification mediated by customer experience and engagement on customer repurchase intention. Samples were selected using a purposive technique by distributing online questionnaires that resulted in 473 valid responses. Data were analyzed using Partial Least Square-Structural Equation Modelling (PLS-SEM). The findings showed the positive effects of gamification on repurchase intention through customer experience and engagement.